Synergistic effects of polymyxin and vancomycin combinations on carbapenem- and polymyxin-resistant Klebsiella pneumoniae and their molecular characteristics - Ozioma Forstinus Nwabor; Arnon Chukamnerd; Pawarisa Terbtothakun; Lois Chinwe Nwabor; Komwit Surachat; Sittiruk Roytrakul; Supayang Piyawan Voravuthikunchai; Sarunyou Chusri (Microbiology Spectrum, 2023)
ABSTRACT The emergence and spread of polymyxin resistance, especially among Klebsiella pneumoniae isolates, threaten the effective management of infections. This study profiled for polymyxin resistance mechanisms and investigated the activity of polymyxins plus vancomycin against carbapenem- and polymyxin-resistant K. pneumoniae. The entire genome sequences of seven isolates were profiled for resistance and virulence determinants. The effects of combination therapy were evaluated using the checkerboard technique, time-kill assay, and population profile analysis. Protein profiles of the isolates treated with monotherapy were compared to that of combination therapy. The whole-genome sequencing data revealed that the isolates harbored β-lactams, carbapenems, aminoglycoside, fluoroquinolones, macrolides, and tetracycline resistance genes, with several virulence-associated genes. The plasmids including the bla OXA-232-bearing ColKP3 plasmid were also identified in our isolates. Profiling for polymyxin resistance mechanism revealed a missense mutation in the crrB gene that resulted in a Q180L variant that conferred a deleterious effect on protein function. The combination assay indicated fractional inhibitory concentration index ranging from 0.31 to 1.13, whereas the time-kill assay demonstrated synergistic log reduction in colony-forming units per milliliter. Furthermore, population analysis profiling using dual antibiotics indicated enhancement in bacterial log reduction at lower antibiotics concentrations, compared to higher concentrations of single polymyxins. For protein profiling, 796 proteins were identified, and 56 and 94 of them were increased and decreased in the combined drug treatment groups, respectively, while other differentially produced proteins were detected in all treatment groups, except for the control group. The results demonstrated that the vancomycin combination might benefit the antimicrobial activities of polymyxins. IMPORTANCE This study provides insights into the mechanisms of polymyxin resistance in K. pneumoniae clinical isolates and demonstrates potential strategies of polymyxin and vancomycin combinations for combating this resistance. We also identified possible mechanisms that might be associated with the treatment of these combinations against carbapenem- and polymyxin-resistant K. pneumoniae clinical isolates. The findings have significant implications for the development of alternative therapies and the effective management of infections caused by these pathogens.